Effects of Organic Manures and Foliar Sprays on Growth and Yield of Finger Millet - Sivagamy, K.; Karunakaran, V.; Ananthi , K.; Rajesh, M.; Arul Prasad, S.; Tamilselvi, C.; Vijayashanthi, V.A.; Mohammed Ashraf, A.; Vanitha, K.; Kanaga, S. (Agronomy Journal of Nepal, 2024)
Experiments were conducted at the Centre of Excellence in Millets, Athiyandal, Thiruvannamalai, India to evaluate various organic nutrient sources with foliar application over three seasons from kharif 2015 to 2017 in Split Plot Design (SPD). Applying farmyard manure (FYM) @ 12.5 t ha-1 along with in-situ incorporation of sunhemp green manuring SGM @ 6.50 t ha-1 at 45 days after planting (DAP) resulted in higher grain and straw yields of 2,420 kg ha-1 and 3,549 kg ha-1, respectively. A foliar spray of Panchakavya at a 3% concentration increased grain and straw yields to 2,423 kg ha-1 and 3,338 kg ha-1. The B4 treatment yielded the highest gross income (₹84,724 ha-1), net income (₹55,372 ha-1), and benefit-cost ratio (2.84). Vermicompost application at 5 t ha-1 led to lower gross income. Among the foliar sprays, Panchakavya at 3% produced the highest gross income (₹84,478 ha-1), net income (₹43,534 ha-1), and benefit-cost ratio (2.36), followed by vermiwash at 3%.